Step * 3 of Lemma Taylor-series-converges-everywhere

.....antecedent..... 
1. : ℝ
2. : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x y)  (F[k;x] F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝr0 ≤ r} lim k→∞.r^k (F[k 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. : ℕ+
7. [%4] icompact([r(-m), r(m)])
8. {t:ℝr0 < t} 
9. [r(-m), r(m)] ⊆ (a t, t) 
⊢ ∀r:{r:ℝ(r0 ≤ r) ∧ (r < t)} lim k→∞.r^k (F[k 1;x]/r((k)!)) = λx.r0 for x ∈ (a t, t)
BY
ParallelOp -5 }

1
1. : ℝ
2. : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x y)  (F[k;x] F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝr0 ≤ r} lim k→∞.r^k (F[k 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. : ℕ+
7. [%4] icompact([r(-m), r(m)])
8. {t:ℝr0 < t} 
9. [r(-m), r(m)] ⊆ (a t, t) 
10. {r:ℝ(r0 ≤ r) ∧ (r < t)} 
11. lim k→∞.r^k (F[k 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
⊢ lim k→∞.r^k (F[k 1;x]/r((k)!)) = λx.r0 for x ∈ (a t, t)


Latex:


Latex:
.....antecedent..... 
1.  a  :  \mBbbR{}
2.  F  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}k:\mBbbN{}.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (F[k;x]  =  F[k;y]))
4.  infinite-deriv-seq((-\minfty{},  \minfty{});i,x.F[i;x])
5.  \mforall{}r:\{r:\mBbbR{}|  r0  \mleq{}  r\}  .  lim  k\mrightarrow{}\minfty{}.r\^{}k  *  (F[k  +  1;x]/r((k)!))  =  \mlambda{}x.r0  for  x  \mmember{}  (-\minfty{},  \minfty{})
6.  m  :  \mBbbN{}\msupplus{}
7.  [\%4]  :  icompact([r(-m),  r(m)])
8.  t  :  \{t:\mBbbR{}|  r0  <  t\} 
9.  [r(-m),  r(m)]  \msubseteq{}  (a  -  t,  a  +  t) 
\mvdash{}  \mforall{}r:\{r:\mBbbR{}|  (r0  \mleq{}  r)  \mwedge{}  (r  <  t)\}  .  lim  k\mrightarrow{}\minfty{}.r\^{}k  *  (F[k  +  1;x]/r((k)!))  =  \mlambda{}x.r0  for  x  \mmember{}  (a  -  t,  a  +  t)


By


Latex:
ParallelOp  -5




Home Index